International recommendations for industrial statistics 2008 - United Nations (United Nations, 2011)
The present publication is a component of the United Nations Statistics Division initiative for strengthening countries methodological and operational foundation for industrial statistics. Although this publication makes recommendations for industrial statistics, many elements of its recommendations, like those for the definition and delineation of statistical units and its guidance on a data-collection strategy and data compilation practices, are generally applicable to the development of an integrated economic statistics system for business statistics in general, with a view to collecting, compiling and reporting basic economic data across economic activities, in the most cost-efficient manner, consistent with macroeconomic statistics. This publication is designed to provide a comprehensive methodological framework for the collection and reporting of industrial statistics in all countries, irrespective of the level of development of their statistical systems.